Evolving Constraints in Military Applications using Wireless Sensor Networks (International Journal of Innovative Research in Computer Science & Technology, 2017)
WSNs consist of a large number of small sensor  nodes. These nodes are very cheap in terms of cost. In military  operations, there is always a threat of being attacked by  enemies. So, the use of these cheap sensor nodes will help to  reduce the loss. In this paper, we analyze the existing literature  of using WSNs for military applications. We will discuss the  available scenarios of using sensor nodes in the military uses.  Provided suitable sensors the system can detect identify and  classify threads based on the count, number, type weather it is  armored vehicles or men in foot, type and amount of weapons  they carry, etc., can be detected in advance. This system  provides reliable real time war picture and better situational  awareness. This will further help to improve the troop  readiness and decrease the reaction time. Added using the data  collected tactical planning for deploying troops effectively can  be done. In case of civil applications economic zones like oil  fields, gold mines, can be protected from intruders and  attackers. Industrial complex and production facility can be  protected with minimized man power and improved efficiency.  Basic criteria are which had to be taken into account while  deploying wireless sensors for such applications has been  discussed. Particularly locating the intruder with respect to  the distance from the sensor node to the target in terms of  latitude and longitudinal coordinates are discussed here.
Keywords: Radar signals; quantization error; friend identification; power management; perimeter defense